Spatial-Temporal Distribution of Allelopathic Rice Roots in Paddy Soil and Its Impact on Weed-Suppressive Activity at the Seedling Stages - Li, Jiayu; Lin, Shunxian; Ma, Huayan; Wang, Yanping; He, Haibin; Fang, Changxun (Frontiers in Plant Science, 2022)
Background: Allelochemicals secreted by allelopathic rice roots are transmitted to receptor rhizosphere through soil medium to inhibit surrounding weeds. This research aimed to explore the relationships between spatial-temporal distribution of rice roots in soil and weed-suppression ability at its seedling stage. Results: This study first examined root distribution of three rice cultivars in paddy soil with both vertical and horizontal directions at 3-6 leaf stages. Then, the experiment of rice-barnyardgrass mixed culture was conducted to analyze allelopathic potential and allelochemicals contents secreted by rice roots in different lateral soil layers. The results showed that allelopathic rice had smaller root diameter and larger root length density, root surface area density, root dry weight density than that of non-allelopathic rice, in the top 5 cm at 5-, and 6-leaf stage. In particular, there was significant differences in root distribution at the horizontal distance of 6-12cm. Besides, allelopathic rice significantly inhibited above-ground growth of barnyardgrass co-cultured at 12cm lateral distance in situ, and benzoic acid derivatives contents of allelopathic rice in 6-12cm soil circle were higher than that at 0-6cm distance. Moreover, correlations analysis confirmed root distribution at horizontal distance were significantly correlated with weed inhibition effect and allelochemicals contents. Conclusions: These results implied spatial distribution of allelopathic rice roots in paddy soil, especially at the lateral distance, appears to have important impacts on its weed-suppressive activity at the seedling stage, suggesting that modifying root distribution in soil may be a novel method to strength the ability of rice seedlings to resist paddy weeds.